2009
DOI: 10.1099/vir.0.006825-0
|View full text |Cite
|
Sign up to set email alerts
|

Partial molecular characterization of alphaherpesviruses isolated from tropical bats

Abstract: Herpesviruses have previously been isolated from African and South-American bats. Recently, herpesviruses detected from European insectivorous bats (family Vespertilionidae) were classified molecularly as betaherpesviruses and gammaherpesviruses. In the current study, we performed PCR analyses targeting the UL30 catalytic subunit region of the DNA polymerase gene of the African and South American herpesviruses and new Malagasy and Cambodian herpesviruses isolated from bats, especially frugivorous bats from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 9 publications
3
46
0
Order By: Relevance
“…nathusii ). Razafindratsimandresy et al also reported the detection of the same herpesvirus in two bats of the same genus Eidolon , with distinct distribution areas [6]. On the other hand, our study shows that more than one herpesvirus could be hosted by same bat species.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…nathusii ). Razafindratsimandresy et al also reported the detection of the same herpesvirus in two bats of the same genus Eidolon , with distinct distribution areas [6]. On the other hand, our study shows that more than one herpesvirus could be hosted by same bat species.…”
Section: Discussionsupporting
confidence: 50%
“…No alphaherpesviruses were detected in this study nor in the study by Wibbelt et al [7] who analyzed bat lung tissues. However, evidence of alphaherpesviruses in other bats has recently been provided from spleen tissues of Indonesian fruitbats [5], and from throat swabs and salivary glands of other fruit bats from the genera Eidolon and Pteropus [6]. The absence of alphaherpesviruses in bats aside from fruit bats could indicate that bat alphaherpesviruses evolved only in the Pteropodidae family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Since the first investigations carried out by the Institut Pasteur in the 1970s, 16 arboviruses or related viruses have been isolated in Madagascar. 9,[11][12][13] CCHFV is the only member of the genus Nairovirus detected in the island. However, we cannot exclude the presence of an undected nairovirus close to CCHFV like viruses from the Nairobi sheep disease group including the eponym virus and Dugbe virus, present and widespread in continental Africa (http://www.cdc.gov/nczved/divisions/dvbid/arbovirus.html).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The genus Simplexvirus includes 7 human or primate viruses. 3 The remaining members include Bovine herpesvirus 2 (BoHV-2), 2 wallaby viruses, and recently described frugivorous bat (Eidolon) viruses, 3,5,7,12 but these viruses also do not fit the model of herpesvirus/host co-evolution. The data indicate that members of Simplexvirus co-evolved with their primate and human hosts approximately 78 million years ago, 8,9 whereas phylogenetic divergence of cattle and bats, hyraxes, and marsupials occurred approximately 87, 103, and 130 million years ago, respectively.…”
mentioning
confidence: 99%